Impact of standard of care treatments and disease variables on outcomes in systemic lupus erythematosus trials: analysis from the Lupus Foundation of America Collective Data Analysis Initiative - Kalunian, Kenneth Carekin (Eur J Rheumatol, 2016)
OBJECTIVE: Most clinical trials for systemic lupus erythematosus (SLE) study the efficacy and safety of investigational agents added to variable background immunosuppressants, which has resulted in high response rates in patients treated with placebo plus standard of care (SOC) plus rescue measures. This project compared the impact of different SOC treatments and disease variables on the outcomes of SLE trials. MATERIAL AND METHODS: Data were obtained from 981 patients receiving only SOC treatments in three nephritis and three general SLE trials to compare response and flare rates on the basis of the British Isles Lupus Assessment Group (BILAG) index, a measure common to all trials. RESULTS: For subjects enrolled in general SLE trials (n=173), those receiving mycophenolate mofetil (MMF) had more severe baseline disease, included more patients of African descent, and were administered higher baseline steroid doses compared with those receiving azathioprine (AZA) or methotrexate (MTX). BILAG responses at week 12 were MMF 35%, AZA 49%, MTX 34%, and no immunosuppressant (NIS) 65%. At week 52, MMF response rates increased to 41% despite reducing the steroid doses, but fell in all others (p=0.07, adjusted for steroids). Patients with severe disease activity at baseline (SDAB) who were defined as ≥1 BILAG A (severe) organ score had lower response rates to AZA or MTX but higher rates to MMF or NIS. Interim flares were highest with MMF [flares/patient–year (pt–yr)]. For all flares, rates were as follows: AZA 1.24, MMF 1.87, MTX 1.42, and NIS 0.81 and severe flares were as follows: AZA 0.66, MMF 1.29, MTX: 1.20, and NIS 0.55. Interim flares occurred in 71% of MMF-endpoint responders, 54% of AZA, 50% of MTX, and 22% of NIS. Patients with SDAB had more flares than moderate patients in the MMF and MTX groups: MMF: 2.39 vs. 1.03 flares/pt–yr (p=0.01), MTX: 2.33 vs. 0.63 (p=0.0002), severe flares: 1.87 vs. 0.34 for MMF (p=0.0013), 2.13 vs. 0.40 for MTX (p<0.0001). In nephritis trials (n=808), MMF subjects received less steroids than intravenous cyclophosphamide and response rates were similar, but MMF-treated patients had fewer severe flares (p=0.03). CONCLUSION: Compared with MMF, AZA and MTX were associated with lower response rates at week 52. AZA-treated subjects had fewer flares and remained more stable in trials while engendering lower placebo plus SOC responses. MMF-treated subjects had frequent responses but more flares, suggesting that flares should be included in endpoint definitions. Given the likelihood of treatment selection bias, these data do not provide conclusions regarding efficacy but may help future trial designs by distinguishing factors definable at entry that are predictive of outcomes.